Quantifying Local and Mesoscale Drivers of the Urban Heat Island of Moscow with Reference and Crowdsourced Observations - Varentsov, Mikhail; Fenner, Daniel; Meier, Fred; Samsonov, Timofey; Demuzere, Matthias (Frontiers in Environmental Science, 2021)
Urban climate features such as the urban heat island (UHI) are determined by various factors characterizing the modifications of the surface by the built environment and human activity. These factors are often attributed to the local spatial scale (hundreds of meters up to several kilometers). Nowadays, more and more urban climate studies utilize the concept of the Local Climate Zones (LCZs) as a proxy for urban climate heterogeneity. However, for modern megacities that extend for dozens of kilometers, it is reasonable to suggest a significant contribution of the larger-scale factors to the temperature and UHI climatology. In this study, we investigate the contribution of local-scale and mesoscale driving factors of the nocturnal canopy-layer UHI of Moscow megacity in Russia. The study is based on air-temperature observations from a dense network consisting of around 80 reference and more than 1500 crowdsourced citizen weather stations for a summer and a winter season. For crowdsourcing data, an advanced quality-control algorithm is proposed. Based on both types of data, we show that the spatial patterns of the UHI are shaped both by local-scale and mesoscale driving factors. The local drivers represent the surface features in the vicinity of a few hundred meters and can be described by the LCZ concept. The mesoscale drivers represent the influence of the surrounding urban areas in the vicinity of 2-20 km around a station, transformed by diffusion and advection in the atmospheric boundary layer. The contribution of the mesoscale drivers is reflected in air-temperature differences between similar LCZs in different parts of the megacity and in a dependence between the UHI intensity and the distance from the city center. Using high-resolution city-descriptive parameters and different statistical analysis, we quantified the contributions of the local- and mesoscale driving factors. For selected cases with a pronounced nocturnal UHI effect their respective contributions are of similar magnitude. Our findings highlight the importance of taking both local- and mesoscale effects in urban climate studies for megacities into account. Further, they underscore a need for an extension of the LCZ concept to take mesoscale settings of the urban environment into account.